Flood Prone Areas Mapping using Remote Sensing and GIS Techniques in Kalal Badrah Basin, Wasit, East of Iraq - Athraa Abbas Kadhim; Marwa Razzaq Aya; Zainab N. Jasim (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Floods are considered one of the most dangerous natural disasters globally due to the damage they cause, impacting lives and damaging property, infrastructure, and economic activities. Despite the increasing frequency of flash floods in Iraq, particularly in the eastern regions, as a result of climate change, high-resolution spatial assessments remain limited. This study addresses this research gap by integrating the latest Landsat 9 satellite imagery and rainfall data from the Global Precipitation Measurement System (GPM IMERG) within a multi-criteria framework based on geographic information systems (GIS) for the Kalal Badra Basin. The scientific contribution lies in providing a local sensitivity map with a 30-meter resolution that classifies the basin into three risk zones, offering a vital tool for disaster mitigation in data-poor semi-arid environments. The study guides methodology based on DEM SRTM, Landsat image, GPM data. The approach described integrates remote sensing and GIS techniques. Various thematic layers such as slope, elevation, Normalized Difference Vegetation Index (NDVI), drainage density and precipitation were employed to delineate flood prone zones in the Kalal Badrah watershed in Iraq. The individual flood susceptibility maps of each thematic layer were combined with equal weights within the GIS environment to generate the overall flood susceptibility map of the study area. The final map classified the study area to three classes: No flood risk, low flood risk, and high flood risk area according to the selected criteria.